(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2026)
The order of the universal of human life is no longer natural, because during this time, humans live in a world full of the hustle and bustle of economic and political transaction that have exceeded the limits of space and time. Karl Polanyi in his intelectual struggle, showed a paradox: What we enjoy in this world is something was not natural. The extraordinary changes that have occured this century are a design. Economics, politics, the concept of human rights, and political freedom or democratic government are part of the rhetoric of this limitation. However, in addition to the design of the current rhetorical arguments, society lives in a world of extraordinary deprivation, poverty, and oppression. Various problem, both new and old, are mixed together and can no longer be separated. Poverty, unmet basic needs, widespread hunger, violations of political freedom, and legal transaction have finally become banal. Polanyi gives us a basis for thinking about history and internal logic of economics because only this way, we can understand that social problem such as restrictiveness access to the saturated, scarcity, and the failure to fully satisfy society’s needs are rhetorical design so that problems are sounds like a natural event.